Upward Bound Program Supports Success of Low-Income and/or First-Generation College Students at a STEM-Focused HSI - Brooklin Hensley; Theresa Apodaca; Megha Khandelwal (MDPI AG, 2024)
A deeper understanding of low-income and first-generation college student experiences is essential to advancing diversity and equity in higher education. Due to a significant gap in college enrollment and graduation rates for low-income and first-generation college students, specifically after COVID-19, it is important to identify factors affecting their success. The Upward Bound Math and Science (UBMS) Program at New Mexico Tech (NMT) supports high school students who are either first-generation college students and/or from low-income families to prepare them with the skills and motivation necessary to complete high school and enter and succeed in a program of postsecondary education. These students face unique challenges during their time at college. To identify the factors that affect the success of these students, we surveyed several of our UBMS program participants who chose to attend NMT after completing high school. All participants said support from UBMS staff was critical when starting college at NMT. Participants also mention building a support system with their fellow UBMS alumni to deal with the struggles that being at STEM-focused institutions brings. This study also resulted in several suggestions for faculty and staff members to improve academic outcomes for all students.